2015
DOI: 10.1039/c5py00006h
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular charge-transfer emission from conjugated polymer nanoparticles: the terminal group effect on electronic and optical properties

Abstract: Efficient tuning of electronic and optical properties of conjugated polymer nanoparticles by intramolecular charge transfer between the core and the terminal groups is demonstrated for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Many fluorescent-based moisture sensors are available in the literature based on different kinds of mechanisms such as fluorescence intensity change, ratio fluorescence, solvatochromism, and so on. Besides organic probes, some luminescent nanomaterials-based sensors for water detection have also been developed . For example, covalent organic frameworks (COFs), carbon quantum dots, metal–organic frameworks (MOFs), copper nanoclusters, and other nanomaterials have been reported for sensing water in organic solvents.…”
mentioning
confidence: 99%
“…Many fluorescent-based moisture sensors are available in the literature based on different kinds of mechanisms such as fluorescence intensity change, ratio fluorescence, solvatochromism, and so on. Besides organic probes, some luminescent nanomaterials-based sensors for water detection have also been developed . For example, covalent organic frameworks (COFs), carbon quantum dots, metal–organic frameworks (MOFs), copper nanoclusters, and other nanomaterials have been reported for sensing water in organic solvents.…”
mentioning
confidence: 99%
“…The fluorescence emission spectra of Ta‐CMPs were obtained using their dispersion in various solvents (2 mg per 10 mL), including n ‐hexane (HEX), TOL, dichloromethane (DCM), THF, and DMF (Figure c). With an excitation wavelength of 365 nm, the maximum emissions of Ta‐CMP, Ta‐CMP‐N, and Ta‐CMP‐CN show red‐shift with the increase of solvent polarity, which proves the intramolecular charge transfer (ICT) effect of the polymers …”
Section: Resultsmentioning
confidence: 94%
“…[ 39 ] Zhang et al reported a series of new conjugated polymer fluorescent probes. [ 40 ] However, conjugated polymer synthesis methods are mainly about Suzuki coupling, [ 41,42 ] Yamamoto reaction, [ 43 ] Kumada reaction, [ 44 ] Heck reaction, [ 45 ] Sonogashira reaction. [ 46,47 ] These reactions are used in the process of non‐environmentally friendly solvents and heavy metal catalyst.…”
Section: Introductionmentioning
confidence: 99%